KAJIAN PENERAPAN MODEL-MODEL KOOPERATIF PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN TUMBUHAN - Yuliani, Riska; Nazira, Diva; Agustina, Elita (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
Plant growth and development materials contain abstract concepts that require in-depth understanding. This study aims to examine the improvement of research parameters using a cooperative model on plant growth and development material. The research method used literature study with secondary data from research articles. Data were presented in tabular form and analyzed descriptively. The results showed that learning models such as discovery learning, problem-based learning, guided inquiry, and cooperative method of Two Stay-Two Stray (Ts-Ts) type were used in plant growth and development material. The application of cooperative models can improve students' activities, learning outcomes, and interest in the material of plant growth and development.Key words: Learning activity, learning outcomes, plant growth and development material, learning models.